A universal GlycoDesign for lysosomal replacement enzymes to improve circulation time and biodistribution - Chen, Yen-Hsi; Tian, Weihua; Yasuda, Makiko; Ye, Zilu; Song, Ming; Mandel, Ulla; Kristensen, Claus; Povolo, Lorenzo; Marques, André R. A.; Čaval, Tomislav; Heck, Albert J. R.; Sampaio, Julio Lopes; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Currently available enzyme replacement therapies for lysosomal storage diseases are limited in their effectiveness due in part to short circulation times and suboptimal biodistribution of the therapeutic enzymes. We previously engineered Chinese hamster ovary (CHO) cells to produce -galactosidase A (GLA) with various N-glycan structures and demonstrated that elimination of mannose-6-phosphate (M6P) and conversion to homogeneous sialylated N-glycans prolonged circulation time and improved biodistribution of the enzyme following a single-dose infusion into Fabry mice. Here, we confirmed these findings using repeated infusions of the glycoengineered GLA into Fabry mice and further tested whether this glycoengineering approach, Long-Acting-GlycoDesign (LAGD), could be implemented on other lysosomal enzymes. LAGD-engineered CHO cells stably expressing a panel of lysosomal enzymes [aspartylglucosamine (AGA), beta-glucuronidase (GUSB), cathepsin D (CTSD), tripeptidyl peptidase (TPP1), alpha-glucosidase (GAA) or iduronate 2-sulfatase (IDS)] successfully converted all M6P-containing N-glycans to complex sialylated N-glycans. The resulting homogenous glycodesigns enabled glycoprotein profiling by native mass spectrometry. Notably, LAGD extended the plasma half-life of all three enzymes tested (GLA, GUSB, AGA) in wildtype mice. LAGD may be widely applicable to lysosomal replacement enzymes to improve their circulatory stability and therapeutic efficacy.